Temporally and spatially dynamic redox conditions on an upwelling margin: The impact on coupled sedimentary Mo and U isotope systematics, and implications for the Mo-U paleoredox proxy. (15th September 2021) - He, Zhiwei; Clarkson, M.O.; Andersen, M.B.; Archer, Corey; Sweere, Tim C.; Kraal, Peter; Guthauser, Alex; Huang, Fang; Vance, Derek
Abstract: The abundances and isotope compositions of molybdenum (Mo) and uranium (U) in ancient sediments are promising tracers of the redox state of the past ocean, whose basis lies in the environmentally dependent Mo and U isotope signatures in modern oceanic settings. Despite their dominance in oceanic budgets, the controls on the Mo-U systematics of upwelling margin sediments remain to be fully understood. Here we present a comprehensive sediment-porewater Mo and U isotope study in the Benguela upwelling system off Namibia, including the first dataset incorporating coupled Mo-U abundance and isotope analysis of both solid authigenic phases and porewaters. The investigated stations represent shelf-to-slope settings, which lie on the upper edge, within and below the oxygen minimum zone (OMZ) of the South Atlantic. The sediments across all stations share similar characteristics: both Mo and U show increasing authigenic enrichment with depth, coupled to an overall decrease in δ 98 Moauth (from ~2.0‰ to 1.3‰ and from ~2.0‰ to 0.3‰) and increase in δ 238 Uauth (from −0.18‰ to 0.05‰ and from −0.34‰ to −0.21‰). Nevertheless, the extents of Mo and U enrichment and associated isotopic fractionations display spatial variability across the OMZ, reflecting variations in local sedimentary redox conditions. Porewater Mo and U concentration patterns are more complex, exhibiting peaks in Mo and U abundance well in excess of seawater (up to 8 times seawater for Mo) associated with correlated shifts in isotope composition. As a result, porewaters exhibit a wide range in isotope compositions, between 0.90‰ and 2.79‰ for δ 98 Mo and between −1.74‰ and 0.26‰ for δ 238 U. Porewater gradients at the time of sampling are inconsistent with diffusion downwards across the sediment–seawater interface as a means of enrichment of the sediment-porewater system. Though these sampled conditions may represent only a snapshot, so that periodically more reducing conditions could lead to concentration gradients that do permit downward diffusion, the data are also readily explained by addition of Mo and U to the sediment-porewater system in particulate form, also under more reducing conditions than at the time of sampling. For example, sequestration of Mo and U to particulate matter as a result of the presence of intermittent sulfide, either in bottom water or in porewater right at the sediment–water interface, explains much of the geochemical and isotope data. The data thus suggest that the early diagenetic enrichment of Mo and U in sediments of upwelling margins is strongly governed by temporal redox fluctuations. Early diagenesis under these dynamic redox conditions on the Namibian upwelling margin are strongly reflected in Mo-U co-variation patterns, as well as anti-correlations between authigenic δ 98 Mo and δ 238 U in sediments. Overall, our new data demonstrate that early diagenetic processes on open-marine continental margins reproduce patterns previously observed for coupled Mo-U isotope systematics in restricted and semi-restricted basins, but via a different set of processes and with important implications for the use of such a coupled approach in the study of ancient marine anoxia.